Aposematism in mammals. (1st October 2021) - Howell, Natasha; Sheard, Catherine; Koneru, Manisha; Brockelsby, Kasey; Ono, Konatsu; Caro, Tim
Abstract: Aposematic coloration is traditionally considered to signal unpalatability or toxicity. In mammals, most research has focused on just one form of defense, namely, noxious anal secretions, and its black‐and‐white advertisement as exemplified by skunks. The original formulation of aposematism, however, encompassed a broader range of morphological, physiological, and behavioral defenses, and there are many mammal species with black‐and‐white contrasting patterns that do not have noxious adaptations. Here, using Bayesian phylogenetic models and data from 1726 terrestrial nonvolant mammals we find that two aspects of conspicuous coloration, black‐and‐white coloration patterns on the head and body, advertise defenses that are morphological (spines, large body size), behavioral (pugnacity), and physiological (anal secretions), as well as being involved with sexual signaling and environmental factors linked to crypsis. Within Carnivora, defensive anal secretions are associated with complex black‐and‐white head patterns and longitudinal black‐and‐white body striping; in primates, larger bodied species exhibit irregular patches of black‐and‐white pelage; and in rodents, pugnacity is linked to sharp countershading and irregular blocks of white and black pelage. We show that black‐and‐white coloration in mammals is multifunctional, that it serves to warn predators of several defenses other than noxious anal secretions, and that aposematism in mammals is not restricted to carnivores.